Strategi Penguatan Domain Partisipasi dan Kepemimpinan dalam Implementasi Kebijakan Pembangunan Pemuda di Kota Sukabumi - Rika Mustikawati; Noorsyamsya Djumara; Nita Nurliawati (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
This research is focused on strengthening the domain of participation and leadership in the implementation of youth development policies in Sukabumi City. Aims to find out how the implementation of youth development policies, the factors causing the low participation and leadership domain, and furthermore to find out what strategies are most appropriate for strengthening the participation and leadership domains. This study uses qualitative methods and SWOT analysis to clearly reveal the phenomena in the implementation of youth development policies in Sukabumi City. Data were collected through documentation studies, observations, and interviews. The collected data is analyzed and processed to produce a strategy. The results showed that the communication process was not optimal because it had not yet reached the villages. Human resources are sufficient in terms of numbers but not adequate in term of competence, budget allocation for youth is still very small, but has adequate facilities and infrastructure. The attitude of the implementors is good and supports the implementation of youth development policies, and the bureaucratic structure has fragmentation. From the results of interviews, documentation studies, and observations, it is known that the causes of low participation and leadership domains namely, the age limit 16- 30 years of youth has not been optimally applied in youth organizations, youth lack access to youth information, and the government has not maximally provided space for youth to participate in meetings. The analysis was carried out using SWOT analysis with internal analysis coordinates 0,21 and external analysis coordinates 0,31 so that the recommended strategy is in quadrat 1 (one), namely formulating activities that encourage youth to participate, collaboration between youth and regional officials, coordination with youth organizations in institutional strengthening.